2007
DOI: 10.1152/ajpregu.00805.2006
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of blood oxygenation during pregnancy in Andean and European residents of high altitude

Abstract: High altitude decreases birth weight, but this effect is diminished in long vs. short-resident, high-altitude populations. We asked whether women from long vs. short-resident, high-altitude populations had higher arterial oxygenation levels by comparing 42 Andean and 26 European residents of La Paz, Bolivia (3,600 m), serially during pregnancy (weeks 20, 30, and 36) and again 4 mo postpartum. Pregnancy raised hypoxic ventilatory sensitivity threefold, resting ventilation (V E), and arterial O2 saturation (SaO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 31 publications
1
56
0
4
Order By: Relevance
“…Vargas (2007) 40 Whittaker (1996) 38 Whittaker (1993) 37 Abudu (1988) 30 Abudu (1985) 14 Rajalakshmi (1985) 32 Bruinse (1985) 44 Hunyor (1982) 46 Pirani (1973) 7 Pirani (1973) 7 Blanche Butler (1968) 34 Hytten (1963) 5 Paintin (1962) 27 Berlin (1953) 39 Whittaker (1996) 38 Whittaker (1993) 37 Bruinse (1985) 44 Rajalakshmi (1985) 32 Abudu (1985) 14 Gibson (1973) 47 Pirani (1973) 7 Blekta (1970) 35 Blanche Butler (1968) 34 Rovinsky (1965) 51 Hytten (1963) 5 Hytten (1963) 5 Berlin (1953) 39 Berlin (1953) Only first author of each study is given. Some studies appear more than once within a gestational-age interval because they provided data for different gestational weeks within that interval.…”
Section: No Statistically Significant Association Was Found Between Mmentioning
confidence: 99%
“…Vargas (2007) 40 Whittaker (1996) 38 Whittaker (1993) 37 Abudu (1988) 30 Abudu (1985) 14 Rajalakshmi (1985) 32 Bruinse (1985) 44 Hunyor (1982) 46 Pirani (1973) 7 Pirani (1973) 7 Blanche Butler (1968) 34 Hytten (1963) 5 Paintin (1962) 27 Berlin (1953) 39 Whittaker (1996) 38 Whittaker (1993) 37 Bruinse (1985) 44 Rajalakshmi (1985) 32 Abudu (1985) 14 Gibson (1973) 47 Pirani (1973) 7 Blekta (1970) 35 Blanche Butler (1968) 34 Rovinsky (1965) 51 Hytten (1963) 5 Hytten (1963) 5 Berlin (1953) 39 Berlin (1953) Only first author of each study is given. Some studies appear more than once within a gestational-age interval because they provided data for different gestational weeks within that interval.…”
Section: No Statistically Significant Association Was Found Between Mmentioning
confidence: 99%
“…This rationale stemmed from previous studies in which we were not able to accurately predict non-Andean ancestry using Hispanic surnames. More specifically, in some cases, even women with two non-Andean, Hispanic surnames (e.g., Garcia) were found to be 100% Amerindian according to ancestry informative genetic markers (39). By contrast, Andean surname frequency (e.g., Condori, Mamani, or Huanca) is strongly correlated with high altitude in Bolivia (39,40).…”
Section: Ancestry Classificationmentioning
confidence: 99%
“…Infant ancestry was classified retrospectively using parental surnames with a methodology validated by gene markers, as described elsewhere (39). Surnames were classified as "Andean" if they were of Aymara or Quechua origin, "Foreign" if they were non-Andean and nonHispanic, and "Mestizo" for all other cases.…”
Section: Ancestry Classificationmentioning
confidence: 99%
“…Previously we have shown that uterine artery (UA) diameter and blood flow are lower near term in women residing at high (3,100 m; 10,170 ft, Leadville) compared with low altitude (1,600 m; 5,280 ft, Denver) in Colorado (36). Greater maternal arterial oxygen content and/or UA blood flow, both of which are determinants of uteroplacental oxygen delivery, are associated with protection from SGA at high altitude (20,28,32,35,36). The frequency of preeclampsia, another condition in which UA blood flow is reduced, also increases with altitude and is responsible for approximately one-half of the altitude-associated reduction in birth weight, further demonstrating the importance of adequate UA blood flow to fetal growth at high altitude (13,15).…”
mentioning
confidence: 98%